Voice Search of Structured Media Data - Song, Young-In; Wang, Ye-Yi; Ju, Y. C.; Seltzer, Mike; Tashev, Ivan; Acero, Alex (International Conference on Acoustics, Speech and Signal Processing, 2009)
This paper addresses the problem of using unstructured queries to search a structured database in voice search applications. By incorporating structural information in music metadata, the end-to-end search error has been reduced by 15% on text queries and up to 11% on spoken queries. Based on that, an HMM sequential rescoring model has reduced the error rate by 28% on text queries and up to 23% on spoken queries compared to the baseline system. Furthermore, a phonetic similarity model has been introduced to compensate speech recognition errors, which has improved the end-to-end search accuracy consistently across different levels of speech recognition accuracy.